Severe fibrotic changes and altered expression of angiogenic factors in maternal scleroderma: placental findings. Issue 2 (30th March 2009) - Ibba-Manneschi, L; Manetti, M; Milia, A F; Miniati, I; Benelli, G; Guiducci, S; Mecacci, F; Mello, G; Di Lollo, S; Matucci-Cerinic, M
Abstract : Objective: Pregnant women with systemic sclerosis (SSc; scleroderma) have an increased risk of premature delivery and small full-term infants. During placental development, angiogenesis and vascular remodelling are essential for a successful pregnancy outcome. An analysis was made of the pathological changes and expression of angiogenic factors in SSc placentas. Methods: Placenta biopsies were obtained from three patients with SSc and four healthy uncomplicated pregnancies after delivery at 34–38 weeks of gestation. The sections were stained with Masson's trichrome and phosphotungstic-acid-haematoxylin and immunostained for connective tissue growth factor (CTGF), α-smooth muscle actin (α-SMA), vascular endothelial growth factor (VEGF), placenta growth factor (PlGF) and receptors VEGFR-1 and VEGFR-2. Results: The pathological findings were signs of decidual vasculopathy, increased syncytiotrophoblast knotting, placental infarcts and villous hypoplasia. Severe and diffuse perivascular and stromal fibrosis of decidua and chorionic villi, and extensive deposition of fibrinoid material around decidual vessels and in intervillous spaces were observed. Strong CTGF expression in the vessel wall, decidual cells and fibroblasts and α-SMA+ myofibroblasts were found. VEGF and VEGFR-2 expression was stronger in SSc than in healthy placentas, while VEGFR-1 expression was similar to controls. PlGF immunopositivity was weaker in SSc. Conclusion: In SSc placentas, severe fibrosis and abnormal vascular remodelling were detected. This may result in reduced blood flow leading to deep sufferance of maternal placenta and possible premature delivery.